2023
DOI: 10.3168/jds.2022-22198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yogurt containing probiotics on respiratory virus infections: Influenza H1N1 and SARS-CoV-2

Abstract: Respiratory virus infections are an escalating issue and have become common worldwide. Influenza and COVID-19 are typical infectious respiratory diseases, and they sometimes lead to various complications. In a situation in which no established drug or treatment exists, consumption of proper food might be beneficial in maintaining health against external infections. We studied the potential effects of mixtures of probiotic strains on various viral infections. The purpose of this study was to assess the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This phenomenon aids in controlling respiratory infections, highlighting the gut-lung axis interplay Daniel. The probiotics load in the yogurt can also directly inhibit the pathogens and reduce inflammation, thereby contributing to overall human health and respiratory infection resistance ( 68 ).…”
Section: Therapeutic Effect Of Yogurt On Human Healthmentioning
confidence: 99%
“…This phenomenon aids in controlling respiratory infections, highlighting the gut-lung axis interplay Daniel. The probiotics load in the yogurt can also directly inhibit the pathogens and reduce inflammation, thereby contributing to overall human health and respiratory infection resistance ( 68 ).…”
Section: Therapeutic Effect Of Yogurt On Human Healthmentioning
confidence: 99%
“…Yogurt caused an increase in the survival rate, body weight, and IFN-γ, IgG1, and IL-10 levels against viral infection and a decrease in the inflammatory cytokines TNF-α and IL-6 in influenza H1N1-infected (C57BL/6) mice. Experiments with SARS-CoV-2-infected hamsters demonstrated that their body weights and histopathological findings of the lungs were improved in the yogurt-treated group [49]. Huang and co-workers (2022), via LC-MS/MS, identified 113 peptides released from the major allergens after digestion of yogurt and transportation through Caco-2 cells.…”
Section: Immunoreactivity Of Dairy-fermented Productsmentioning
confidence: 99%